2018
DOI: 10.1016/j.athoracsur.2017.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis for Intraoperative Extracorporeal Membrane Oxygenation Weaning Failure After Lung Transplantation

Abstract: Our results showed that younger donor age, high Pao, and shorter operation time were factors related to successful ECMO weaning in the operating room after LTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Furthermore, graft ischemia time, recipient age, primary indications, preoperative LAS, Pco 2 level, complications, right ventricular function, mechanical ventilation status, surgery time, blood loss, and transfusion were not identified as independent risk factors for ECMO weaning after LTx, which was inconsistent with other studies. Narm et al 16 independent factors related to early ECMO removal at the end of LTx. Baek et al 17 reported that it was more difficult for elderly patients >65 years to take off ECMO in time after LTx.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, graft ischemia time, recipient age, primary indications, preoperative LAS, Pco 2 level, complications, right ventricular function, mechanical ventilation status, surgery time, blood loss, and transfusion were not identified as independent risk factors for ECMO weaning after LTx, which was inconsistent with other studies. Narm et al 16 independent factors related to early ECMO removal at the end of LTx. Baek et al 17 reported that it was more difficult for elderly patients >65 years to take off ECMO in time after LTx.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest antagonizing heparin with halfdose protamine. Recently, Narm et al have shown that increasing donor age, donor PaO 2 and increasing operation duration were independent risk factors of weaning failure from intraoperative ECMO in their experience (62).…”
Section: Ecmo For Intraoperative Supportmentioning
confidence: 96%
“…2,46 Other risk factors for PGD include advanced donor age, prolonged donor mechanical ventilation, donor PaO 2 before lung procurement, and prolonged operative time. 47 A summary of studies examining ECMO prolongation into the postoperative period can be found in Table 4.…”
Section: Postoperative Ecmo In Lung Transplantationmentioning
confidence: 99%